Clinical Significance and Biological Role of HuR in Head and Neck Carcinomas. (28th January 2018) - Levidou, Georgia; Kotta-Loizou, Ioly; Tasoulas, Jason; Papadopoulos, Thomas; Theocharis, Stamatios
Abstract : Background. Hu-antigen R (HuR) is a posttranscriptional regulator of several target mRNAs, implicated in carcinogenesis. This review aims to present the current evidence regarding the biological role and potential clinical significance of HuR in head and neck carcinomas. Methods . The existing literature concerning HuR expression and function in head and neck carcinomas is critically presented and summarised. Results. HuR is expressed in the majority of the examined samples, showing higher cytoplasmic levels in malignant or premalignant cases. Moreover, HuR modulates several genes implicated in biological processes important for malignant transformation, growth, and invasiveness. HuR seems to be an adverse prognosticator in patients with OSCCs, whereas a correlation with a more aggressive phenotype is reported in several types of carcinomas. Conclusions . A consistent role of HuR in the carcinogenesis and progression of head and neck carcinomas is suggested; nevertheless, further studies are warranted to expand the present information.